Response of Medium and Long Duration Boro Rice Variety (Oryza sativa L.) to Nitrogen Fertilizer (The Agriculturists, 2017)
A field experiment was conducted during November 2009-April 2010 in Bangladesh Rice Research Institute, Bangladesh to examine the response of two rice (Oryza sativa L.) varieties (BRRIdhan28 and BRRI dhan29) to six N rates of nitrogen fertilizer viz. 0, 50, 100, 150, 200 and 250 kg ha-1. The experiment was conducted in a RCB design with three replications. Grain yields of both BRRI dhan28 and BRRI dhan29 increased significantly in a quadratic fashion with N rates. The highest grain yields were obtained from 150 kg N ha-1 in both the varieties. More than 1 t ha-1 yield was obtained in BRRI dhan29 (6.34 t ha-1) at the same rate of N indicated BRRI dhan29 as a nitrogen efficient variety. However, the predicted economic optimum doses of N appeared to be 156 and 158 kg ha-1 for BRRI dhan28 and BRRI dhan29, respectively. The grain yield was mainly influenced by the number of panicles per hill, which was found to increase with the increase of N rates in both the varieties. The Agriculturists 2016; 14(2) 48-60